Pathological evaluation of renal complications in children following allogeneic hematopoietic stem cell transplantation: a retrospective cohort study - Ru-Yue Chen; Xiao-Zhong LI; Qiang Lin; Han-Yun Tang; Ning-Xun Cui; Lu Jiang; Xiao-Mei Dai; Wei-Qing Chen; Fan Deng; Shao-Yan Hu; Xue-Ming Zhu (BMC, 2023)
Abstract Background Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is a curative therapy for hematologic malignancies and non-malignant disorders, such as aplastic anemia, fanconi anemia, and certain immune deficiencies. Post-transplantation kidney injury is a common complication and involves a wide spectrum of structural abnormalities, including glomerular (MSPGN, mesangial proliferative glomerulonephritis; FSGS, focal segmental glomerulosclerosis; MPGN, membranoproliferative glomerulonephritis; MCD, minimal change disease), vascular (TMA, thrombotic microangiopathy), and/or tubulointerstitial (TIN, tubulointerstitial nephritis; ATI, acute tubular injury). Renal biopsy is the gold-standard examination for defining multiple etiologies of kidney impairment. Although kidney injury following HSCT has been studied, little is known about the effects of allo-HSCT on renal pathology in pediatric patients. Methods We retrospectively analyzed renal biopsy specimens from children with kidney injury after allo-HSCT and correlated results with clinical data in the last 10 years. Results Among 25 children (18 males and 7 females), three patients had proteinuria indicating nephrotic syndrome (24-hour urinary total protein/weight > 50 mg/kg/d), nine patients had severely reduced estimated glomerular filtration rate (eGFR < 30 ml/min/1.73 m2) and four patients received kidney replacement therapy (KRT). The main pathologies identified from kidney biopsies were MSPGN (n = 12), FSGS (n = 12), MPGN (n = 5), TMA (n = 4), MCD (n = 3), diffuse glomerular fibrosis (DGF, n = 2), ATI and TIN, in isolation or combined with other pathologies. The median follow-up time was 16.5 (0.5 ~ 68.0) months. Three patients died of recurrent malignancy and/or severe infection, one child developed to end-stage renal disease (ESRD), six patients (24%) had elevated serum creatinine (SCr > 100µmol/l) and nine patients (36%) still had proteinuria. Conclusions This study evaluates histomorphologic findings from kidney biopsies of pediatric recipients following allo-HSCT. Detailed evaluation of renal biopsy samples is helpful to elucidate the nature of renal insult, and may potentially identify treatable disease processes.